Karakteristik Metode Sim?’an Santri pada Program Tahf?zh Pesantren Modern Datok Sulaiman Putra - Julianto, Teguh Arafah; Said, Rukman Abdul Rahman; Anzar, Fauzan Dzawilhaj (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
This study discusses the Sim?'an Method of Santri in the tahf?zh Program of Modern Islamic Boarding School. This study aims to determine the characteristics, implications and supporting and inhibiting factors of the sim?'an method of students in the tahf?zh program of Modern Islamic Boarding School Datok Sulaiman Putra Palopo City. The type of research used in this study is qualitative. The results of this study show that 1) There are 3 characteristics of the sim?'an method of students, namely Sim?'an Mukammal, Sim?'an Tasmi and Tasyakuran Sim?'an sugro 30 juz. 2) The application of the sim?'an method has a positive impact on the memorization process, students can mur?ja'ah and increase the constancy of the students' memorization. 3) The existence of facilities is supported for sim?'an activities, there is an increase in the motivation and enthusiasm for reciting the students, maintaining the consistency of togetherness between students, improving the quality of the students' recitation of the Qur'an and becoming a place for mental training of students. Busyness in school learning activities or assignments, as well as the existence of memorized readings that are less than optimal and students are also still less focused when sim?'an has taken place to be an inhibiting factor